Circulating microRNA-409-5p and USP7 are associated with left ventricular remodeling in patients with acute myocardial infarction - Guiping He; Sha Sha; Jiaji He; Xi Zhang; Qing Jin; Tao Zhao; Sheng Jin; Nitesh Shrestha; Hongxia Li; Qiu Chen; Qiang Xue (BMC Cardiovascular Disorders, 2024)
Abstract Background Our previous study demonstrated that microRNA-409-5p (miR-409-5p) and its target ubiquitin-specific protease 7 (USP7) were involved in hypoxia-induced cardiomyocyte injury and ischemic left ventricular remodeling (LVR) in rats. This study aimed to probe into the relationship between plasma miR-409-5p and USP7 levels and LVR and dysfunction in patients with acute myocardial infarction (AMI). Methods Sixty patients with acute myocardial infarction (AMI) and 60 cases with chronic coronary syndrome (CCS) were enrolled. The clinical characteristics, echocardiographic/serum parameters of LVR, and circulating miR-409-5p and USP7 mRNA levels between the two groups and between admission and 6 weeks after discharge were compared. The correlations between circulating miR-409-5p/USP7 levels and serum/echocardiographic parameters were analyzed. Results The demographic characteristics of the AMI group and CCS group were comparable. Patients with AMI admitted to the study displayed significantly higher levels of plasma N-terminal pro-brain natriuretic peptide (NT-proBNP) and growth stimulation expressed gene 2 (ST2), along with a greater left ventricular end-systolic volume (LVESV). Conversely, their left ventricular ejection fraction (LVEF), global longitudinal strain (GLS), and global radial strain (GRS) were significantly lower compared to patients with CCS. These changes were normalized 6 weeks after discharge. Circulating miR-409-5p levels at admission were significantly decreased while circulating USP7 mRNA expression levels were significantly increased in patients with AMI compared with those with CCS (both P < 0.01). However, these changes were restored 6 weeks after discharge (both P < 0.01). Moreover, circulating miR-409-5p and USP7 mRNA levels showed varying correlations with GLS, GRS, LVESV, LVEF, and NT-proBNP in patients with AMI but not in those with CCS. Additionally, circulating miR-409-5p and USP7 levels predicted the incidence of LVR and major adverse cardiovascular events (MACE) after AMI. Conclusion Serum miR-409-5p and USP7 may influence the occurrence and evolution of LVR and left ventricular dysfunction after AMI.